EZH2 as a mediator of treatment resistance in melanoma. (25th May 2016) - Tiffen, Jessamy C.; Gallagher, Stuart J.; Tseng, Hsin‐Yi; Filipp, Fabian V.; Fazekas de St Groth, Barbara; Hersey, Peter
Summary: Direct treatments of cancer such as chemotherapy, radiotherapy and targeted therapy have been shown to depend on recruitment of the immune system for their effectiveness. Recent studies have shown that development of resistance to direct therapies such as BRAF inhibitors in melanoma is associated with suppression of immune responses. We point to emerging data that implicate activation of the polycomb repressive complex 2 (PRC2) and its catalytic component—enhancer of zeste homolog 2 (EZH2)—in progression of melanoma and suppression of immune responses. EZH2 appears to have an important role in differentiation of CD4 T cells and particularly in the function of T regulatory cells, which suppress immune responses to melanoma. We review mechanisms of EZH2 activation at the genomic level and from activation of the MAP kinase, E2F or NF‐kB2 pathways. These studies are consistent with activation of EZH2 as a common mechanism for induction of immune suppression in patients failing direct therapies and suggest EZH2 inhibitors may have a role in combination with immunotherapy and targeted therapies to prevent development of immunosuppression.